1995
DOI: 10.1073/pnas.92.20.9220
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxylation of estradiol by human uterine myometrium and myoma microsomes: implications for the mechanism of uterine tumorigenesis.

Abstract: Estradiol is converted to catechol estrogens via 2-and 4-hydroxylation by cytochrome P450 enzymes. 4-Hydroxyestradiol elicits biological activities distinct from estradiol, most notably an oxidant stress response induced by free radicals generated by metabolic redox cycling reactions. In this study, we have examined 2-and 4-hydroxylation of estradiol by microsomes ofhuman uterine myometrium and of associated myomata. In all eight cases studied, estradiol 4-hydroxylation by myoma has been substantially elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(109 citation statements)
references
References 26 publications
2
102
0
5
Order By: Relevance
“…8 Alterations in estrogen metabolism have been observed in tumor tissues. Microsomes obtained from tumor tissues predominantly catalyze 4-hydroxylation, 39,40 whereas those from normal tissues express comparable estradiol 2-and 4-hydroxylase activities. 40 Therefore, 4-OHE 2 could play a more important role in carcinogenesis than 2-OHE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…8 Alterations in estrogen metabolism have been observed in tumor tissues. Microsomes obtained from tumor tissues predominantly catalyze 4-hydroxylation, 39,40 whereas those from normal tissues express comparable estradiol 2-and 4-hydroxylase activities. 40 Therefore, 4-OHE 2 could play a more important role in carcinogenesis than 2-OHE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ␤E2 in target organs of estrogen-induced cancer is metabolized to 2-and 4-hydroxyestradiol, commonly known as catechol estrogens (16,36,37). Elevated estradiol-4-hydroxylase activity has also been shown in organs that are prone to estradiol-induced hyperplasia or cancer in rodents, in humans, and in human breast cancer cell lines (16,18,(36)(37)(38)(39)(40). Catechol estrogens are orthohydroquinones that are capable of undergoing metabolic redox Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The highest levels of CYP1B1 are found in the endometrium (11). Endometrial myoma tissue has significantly elevated 4-OHE 2 levels compared with the surrounding normal myometrium, an effect that is abrogated by inhibition of CYP1B1 (139). Furthermore, 4-OHE 2 production was shown to be responsible for endometrial carcinoma in mice (87).…”
Section: Mol Cancer Res 2006;4(3) March 2006mentioning
confidence: 99%